2002
DOI: 10.1152/ajpheart.00203.2002
|View full text |Cite
|
Sign up to set email alerts
|

Positive inotropic effects of ouabain in isolated cat ventricular myocytes in sodium-free conditions

Abstract: The inotropic and toxic effects of cardiac steroids are thought to result from Na+-K+-ATPase inhibition, with elevated intracellular Na+(Na[Formula: see text])causing increased intracellular Ca2+(Ca[Formula: see text]) via Na-Ca exchange. We studied the effects of ouabain on cat ventricular myocytes in Na+-free conditions where the exchanger is inhibited. Cell shortening and Ca[Formula: see text] transients (with fluo 4-AM fluorescence) were measured under voltage clamp during exposure to Na+-free solutions [L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
2

Year Published

2003
2003
2008
2008

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 28 publications
1
21
2
Order By: Relevance
“…In the experiments in which I Ca was measured, a low concentration of Ba 2ϩ (0.2 mM) was sufficient to block background K ϩ current but had little effect on magnitude and kinetics of I Ca in the presence of 1.8 mM CaCl 2 . We have used this approach previously (Nishio et al, 2002) and found it to be a useful means to measure I Ca under conditions in which normal physiological conditions are otherwise maintained (physiological [Ca 2ϩ ], temperature, K ϩ gradient). Molecular Structures of the Six Cardiac Glycosides Studied.…”
Section: Methodsmentioning
confidence: 99%
“…In the experiments in which I Ca was measured, a low concentration of Ba 2ϩ (0.2 mM) was sufficient to block background K ϩ current but had little effect on magnitude and kinetics of I Ca in the presence of 1.8 mM CaCl 2 . We have used this approach previously (Nishio et al, 2002) and found it to be a useful means to measure I Ca under conditions in which normal physiological conditions are otherwise maintained (physiological [Ca 2ϩ ], temperature, K ϩ gradient). Molecular Structures of the Six Cardiac Glycosides Studied.…”
Section: Methodsmentioning
confidence: 99%
“…n ϭ 6 myocytes from 2 to 4 cats for each point. strom's group (95) reported that patch-clamped myocytes under Na-free conditions showed increased Ca 2ϩ transient magnitude and a positive inotropic effect in a glycoside-sensitive species (cat) but not in an insensitive species (rat). As a result of these observations made over the last nearly half century, it may still be necessary to consider that Na i ϩ accumulation may not be the only mechanism responsible for all of the cardiac actions of digitalis.…”
Section: Evidence For Additional Cellular Actions Of Digitalismentioning
confidence: 99%
“…Myocytes were loaded with fluo-4AM (5 M for 30 min at room temperature) then washed twice in normal Tyrode's solution before being placed in the experimental chamber and allowed to settle to the laminin-coated coverslip floor. Superfusion was then initiated with Na ϩ -free solution (Li ϩ replacement) which had a low CaCl 2 to prevent cell death due to Ca 2ϩ overload (Nishio et al, 2002). It is not known whether these conditions are sufficient to ensure that cells are completely depleted of Na ϩ ; however, even if some Na ϩ remains in the cell, there is still no external source of Na ϩ that could allow the increase in internal Na ϩ necessary for Na ϩ pump inhibition to contribute to the cellular actions of ouabain.…”
mentioning
confidence: 99%